Physical-socio-economic systems integration for community resilience-informed decision-making and policy selection - Wang, Wanting, author; van de Lindt, John W., advisor; Mahmoud, Hussam, committee member; Guo, Yanlin, committee member; Cutler, Harvey, committee member (Colorado State University. Libraries, 2022)
Natural hazards are damaging communities with cascading catastrophic economic and social consequences at an increasing rate due to climate change and land use policies. Comprehensive community resilience assessment and improvement requires the analyst to develop a model of interacting physical infrastructure systems with socio-economic systems to measure outcomes that result from specific decisions (policies) made. There is limited research in this area currently because of the complexity associated with combining physics-based and data-driven socio-economic models. This dissertation proposes a series of multi-disciplinary community resilience assessment models (e.g., multi-disciplinary disruption assessment and multi-disciplinary recovery assessment) subjected to an illustrative natural hazard across physical infrastructure and socio-economic systems. As illustrative examples, all the proposed methodologies were applied to the Joplin, Missouri, testbed subjected to tornado hazard but are generalizable. The goal is to enable community leaders and stakeholders to better understand the community-wide impacts of a scenario beyond physical damage and further empower them to develop and support short-term and long-term policies and strategies that improve community resilience prior to events. Advancements in multi-disciplinary community resilience modeling can help accelerate the development of building codes and standards to meet the requirements of community-wide resilience goals of the broader built environment, consistent with the performance objectives of individual buildings throughout their service lives.